Kebijakan Hukum dalam Penyelesaian Kewarisan Islam (Analisis Terhadap Beberapa Kebijakan Umar bin al-Khattab) - Elfia Elfia (Institut Agama Islam Negeri (IAIN) Curup, 2017)
The central point in this study is to analyze some of the legal policies ever made by Umar bin al-Khattab in solving the problem of inheritance. Launched this research to formulate fiqh of heritage fill the legal policy when difference estoppel happened to adapt to the spirit of the prevailing of justice in society. On legal policy that took by Prophet companions, God bless them in al-Mawarits, it can be informed of a number of issues, as a matter of reliability and Aul and Radd, Gharrawain, Akdariyah, Musyarakah and al-Kharqa’. Stuck legal policy in settling the issue of inheritance justice for all the heirs, because in the settlement of this matter without conditioning will lead to the problem must be resolved patients to win win solution and does not violate the legal argument of the proposition. Took place this issue in the days of Umar bin al-Khattab, he judged them around, then signed again in the Supreme Court and he judged it. It seems that the Supreme Court of Indonesia has taken flexibility and adaptability in government policy. Like giving the heir of the inheritance hit him with a different religion. Why did Umar bin al-Khththab take a legal policy in solving the inheritance problem? What is the underlying legal policy?Access to data and formulas and find a solution to the problems in this study by using library research, and was done through the relevant issues that have been discussed during data collection. This is a research study on the appropriateness and consistency sentences between theoretical and practical. The approach taken in this study is a qualitative approach in the style of descriptive analysis. It is that some of the policies described in the division of heritage, which spent by the Prophet Companions and scholars (Ulema) of the four schools (Mazhab). The result of your search reveal resolve the issue of inheritance in Islam and settled appropriate to good policy and entrusted interest and do not conflict with a peremptory verses of legal texts. The policies made by Umar bin al-Khattab, in some circumstances are still influenced by the Arab tradition of jahiliyah which requires men to get more rights than women. Keyword : Legal Policy, Inheritance, Umar Bin Al-Khattab